REVITALIZING THE GOVERNANCE OF ISLAMIC PHILANTHROPIC ORGANIZATIONS THROUGH ASSISTANCE IN DEVELOPING STANDARD OPERATING PROCEDURES BASED ON AN EMPOWERMENT MINDSET - Agus Setyawanto; Bachtiar Hariyadi (LPPM Universitas Flores, 2026)
Revitalizing the governance of Islamic philanthropic organizations has become a strategic necessity amid the growing demands for professionalism, transparency, and the sustainability of community empowerment programs. Islamic philanthropic organizations are no longer sufficient to merely implement charity-based services that are consumptive in nature; instead, they need to develop an empowerment mindset as a new paradigm in managing social services oriented toward the empowerment of marginalized communities. This Community Service Program aimed to revitalize the governance of Islamic philanthropic organizations through assistance in developing administrative and service Standard Operating Procedures (SOPs) for autonomous bodies under the Yatim Mandiri Foundation operating in the fields of National Zakat Institutions (LAZNAS) and waqf management in Indonesia. The implementation method employed a participatory empowerment approach through observation, training, Focus Group Discussions (FGDs), SOP drafting assistance, implementation simulations, and program evaluation. The results demonstrated an improvement in administrators’ capacity to understand modern organizational governance, the systematic development of administrative and service SOPs, and increased awareness among administrators of the importance of transforming services from charity-oriented to empowerment-oriented approaches. The assistance program also encouraged the emergence of a more professional, collaborative, and long-term social impact-oriented organizational culture through the strengthening of productive zakat and productive waqf programs. Therefore, revitalizing organizational governance through SOP assistance based on an empowerment mindset not only strengthened the institution’s administrative system but also became a strategic effort to transform the organizational culture of Islamic philanthropy into one that is more adaptive, participatory, and sustainable.